THE EFFECT OF PROBLEM BASED LEARNING MODEL ON STUDENT MATHEMATICS LEARNING OUTCOMES VIEWED FROM CRITICAL THINKING SKILLS - Mulyanto, Heri; Gunarhadi, Gunarhadi; Indriayu, Mintasih (International Online Journal of Education and Teaching, 2018)
This study aims to determine the effect of applying problem based learning model on students' mathematics learning outcomes viewed from critical thinking skills of fifth grade students of the private primary school in the Surakarta region. This research is an experimental research using sample of 309 students consisting of experimental class of 153 students and control class of 156 students. Method of data analysis using Two-Way Anova. Results of this study indicate (1) There are significant differences in mathematics learning outcomes between students who following Problem Based Learning model with conventional model (2) There is a significant difference in mathematics learning outcomes between students who have high and low critical thinking skills. (3) There is no interaction effect between learning model and critical thinking skills on mathematics learning outcomes.